Den Begriff "Rasse" überwinden Die "Jenaer Erklärung" in der (Hoch-)Schulbildung - Porges, Karl (Verlag Julius Klinkhardt, 2023)
The common concern of the authors of this publication is to offer a variety of ideas and concepts for overcoming the concept of ""race"" against the background of its history. The Jena Declaration of 2019 serves as an impulse to rethink (higher) education nationwide. The focus will be on aspects of the history of science and its central actors as well as on current perspectives of modern educational work critical of racism. Reports by representatives of selected places of learning who place remembrance and dialogue at the centre of their practical work as well as concrete, didactically methodically prepared teaching suggestions (best practice) and suggestions from various school subjects complete the work.